Oligolectic bee species in Northern Europe (Hymenoptera, Apoidea) - Pekkarinen, Antti (Entomologica Fennica, 1997)
Evolution of flower specialization in bees, the concepts of poly-, oligo- andmonolecty are reviewed. About 60 species recorded in the area of Finland and Sweden are regarded as oligolectic. The proportions of oligoleges among all pollen-collecting bee species are about 30 percent in alarge area of central and Northern Europe. The proportion is about 15 percent in the northern boreal area of Finland and Sweden, where the percentage of polylectic bumblebees is much greater than in more southern areas. Of the solitary bee species recorded in Finland and Sweden, 25 arc regarded as narrow oligoleges, of which 6 species collect pollen from Campanula and 5 from Salix. Eusocial Bombus consobrinus is regarded as a facultative narrow oligolege of Aconitum septentrionale and, apparently, this bee species is the only oligolege in northern Europe, whose distribution completely covers that of the pollen plant. The distribution limits of some narrow oligoleges (e.9. Eucera longicornis and Andrena hattorfiana) approximately follow certain frequencies of their principal pollen plants (lathyrus pratensis and Knautia, respectively). Of the oligolectic bee species in Finland, 32 occur on the lists of threatened species of England, southwestern Germany or Poland. Records of E. longicornis and A. hattorfiana from various periods are given as examples of the decline of oligolectic bees in Finland during recent decades.